Writing Urban Spaces: 'Street Graphics and the Law' As Postmodern Design and Ordinance - Amy Mandelker (Washington University Journal of Law & Policy, 2000)
In exploring the writing of urban design in legal ordinance and in literary and theoretical inscriptions, the former Soviet Union and the United States might serve as two extremely opposed examples of a hyper-regulated urban planning ethos on the one hand, and an under-regulated, unconstructed ad hoc laissez-faire situation on the other. In his comparative study of city planning in the Soviet Union and the United States, Daniel R. Mandelker found that despite theoretical differences, actual planning processes were subject to similar pressures. Additional convergences occur in architectural design. In both nations, the historical event of the revolutionary establishment of a new government influenced the creation of and designation of public space, both in subservience to ideological agendas, and in the impulse to assert legitimacy and authority. Therefore, architects and planners of Colonial America and Petrine Russia share an affinity for neo-Classical architecture, as a citation of enduring antiquity.
Keywords: City planning and redevelopment law; Literature; Municipal ordinances; Signage